Are the anatomical traits of stems and leaves good indicators of habitat specificity in closely related Myrtaceae species from Patagonia? - Puntieri, Javier Guido (2023)
The anatomical attributes of young stems and leaves of newly formed shoots were studied for five Patagonian species of Myrtaceae: Amomyrtus luma, Ugni molinae, Luma apiculata, Myrceugenia exsucca and M. ovata var. nannophylla. The latter three species are more common in periodically-flooded areas than the former two. The vascular cambium and the first cork cambium of a shoot become active at about the same time, two months after budbreak. The cork cambium derives from cells located towards the inside of the perivascular fibers in A. luma, L. apiculata and U. molinae, and towards the outside in M. exsucca and M. ovata. Crystals and starch deposits were found in cortex, ray parenchyma and pith of all species. Total vessel area relative to total xylem area was higher in Myrceugenia spp. and L. apiculata than in A. luma and U. molinae. Interspecific differences in leaf anatomy concerned midvein structure and the development or not of substomatal chambers delimited by column-like cells (found only in Myrceugenia spp.). The anatomical traits of young shoots allow the distinction between species of this family and may contribute to explain each species’ ecological affinities.